Circulation of Shiga Toxin-Producing Escherichia coli Phylogenetic Group B1 Strains Between Calve Stable Manure and Pasture Land With Grazing Heifers - van Overbeek, Leonard S.; Wichers, Jan H.; van Amerongen, Aart; van Roermund, Herman J. W.; van der Zouwen, Patricia; Willemsen, Peter T. J. (Frontiers in Microbiology, 2020)
Escherichia coli strains carrying Shiga toxin 1 and 2 (stx 1 and 2), intimin (eae), and haemolysin (ehxA) production genes were found in grass shoot, rhizosphere soil and stable manure samples from a small-scale cattle farm located in the centre of the Netherlands, using cultivation-dependent and independent microbiological detection techniques. Pasture land with grazing heifers in the first year of sampling in 2014 and without grazing cattle in 2015 was physically separated from the stable that housed rose calves during both years. Manure from the stable was applied to pasture via injection into soil once per year in early spring. Among a variety of 35 phylogenetic distinctly related E. coli strains, one large group consisting of 21 closely resembling E. coli O150:H2 (18), O98:H21 (2) and O84:H2 (1) strains, all belonging to phylogenetic group B1 and carrying all screened virulence traits, was found present on grass shoots (10), rhizosphere soil (3) and stable manure (8) in 2014, but not anymore in 2015 when grazing heifers were absent. Presence and absence of these strains, obtained via enrichments, were confirmed via molecular detection using PCR-NALFIA in all ecosystems in both years. We propose that this group of Shiga toxin-producing E. coli phylogenetic group B1 strains was originally introduced via stable manure injection into the pasture. Upon grazing, these potential pathogens proliferated in intestinal track systems of the heifers resulting in defecation with higher loads of the STEC strain onto the grass cover. The STEC strain was further smeared over the field via hooves of the heifers resulting in augmentation of the potential pathogen in the pasture in 2014, whereas in 2015, in absence of heifers, no augmentation occurred and only a more diverse group of potentially mild virulent E. coli phylogenetic group A and B1 strains, indigenous to pasture plants, remained present. Via this model it was postulated that human pathogens can circulate between plants and farm animals, using the plant as an alternative ecosystem. These data indicate that grazed pasture must be considered as a potential carrier of human pathogenic E. coli strains and possibly also of other pathogens.